Factors of Influence of the Power Elites of the North Caucasus on the Processes of National Discourse - A. Yu. Evseev (Управленческое консультирование, 2023)
The article analyzes approaches to the study of regional power elites and their influence on the formation of national discourse. The author presents the results of a study of the network space used by the elites as information, propaganda and image channels. The author, as a review of the results of the monitoring, describes the aspects that have changed the measure and degree of influence of the power elites on the national media discourse over the past year, and also provides the criteria necessary for the formation of the modern information space of the Chechen Republic